The Influence of Brand Image, Product Quality, And Perceived Value on Purchasing Decisions of Honda Scoopy Automatic Motorcycles in Surabaya City - Mukhamad Iksan; R. Yuniardi Rusdianto (Danadyaksa: Post Modern Economy Journal, 2026)
This research aims to determine the influence of brand image, product quality, and perceived value on purchasing decisions of Honda Scoopy automatic motorcycles in Surabaya City. This research uses a quantitative method with primary data. The population of this study consists of consumers who use Honda Scoopy in Surabaya. Data collection was carried out by distributing questionnaires to 150 respondents using a purposive sampling technique with the criteria of consumers who have purchased and used Honda Scoopy. The data obtained were then processed using multiple linear regression analysis with the help of IBM SPSS software. The analysis techniques used include validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results show that partially brand image, product quality, and perceived value have a positive and significant effect on purchasing decisions. Simultaneously, all independent variables also have a significant effect on purchasing decisions, with perceived value as the most dominant variable.